2021
DOI: 10.1039/d1cp02440j
|View full text |Cite
|
Sign up to set email alerts
|

Compositional flexibility in Li–N–H materials: implications for ammonia catalysis and hydrogen storage

Abstract: Li-N-H materials, particularly lithium amide and lithium imide, have been explored for use in a variety of energy storage applications in recent years. Compositional variation within the parent lithium imide,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 45 publications
(57 reference statements)
3
31
0
Order By: Relevance
“…S3, ESI†). This corresponds to the observed upper limit of nitride–hydride incorporation into the solid solution; 20 further formation of stoichiometric Li 4 NH appears to result in rapid hydrogenation to LiH (Fig. S3, ESI†), which reduces the ammonia productivity in subsequent cycles.…”
supporting
confidence: 55%
See 4 more Smart Citations
“…S3, ESI†). This corresponds to the observed upper limit of nitride–hydride incorporation into the solid solution; 20 further formation of stoichiometric Li 4 NH appears to result in rapid hydrogenation to LiH (Fig. S3, ESI†), which reduces the ammonia productivity in subsequent cycles.…”
supporting
confidence: 55%
“…This builds on our recent work where we highlighted the implications of compositional variation in the Li-N-H system for hydrogen storage and ammonia catalysis. 20 More precisely, we revealed the formation of a solid solution with a highly disordered anti-fluorite structure for mixed lithium amide-imide (Li 2Àx NH 1+x , 0 o x o 1) and lithium imide-nitride-hydride (Li 2+x NH, 0 o x o 2) phases. 20 While the former is more extensively studied from a hydrogen storage and release standpoint, 21 the latter solid solution with nitridehydride character is of interest to this study, considering the reported involvement of hydridic hydrogen in electron and hydrogen transfer during ammonia synthesis.…”
mentioning
confidence: 81%
See 3 more Smart Citations